Seriously pink: a cross-cultural examination of the perceived image of rosé wine. Issue 4 (16th November 2015) - Velikova, Natalia; Charters, Steve; Bouzdine-Chameeva, Tatiana; Fountain, Joanna; Ritchie, Caroline; Dodd, Tim H.
Abstract : Purpose: – This paper aims to examine consumer preferences and perceptions of rosé wine with an ultimate purpose of constructing a perceived image of rosé in the cross-cultural context. Design/methodology/approach: – The study was conducted in four markets, comprising the USA, New Zealand, France and the UK. The data were collected via a structured questionnaire through a combination of survey administration modes (pen-and-paper and online). Descriptive statistics, chi-square, factor analysis and ANOVA were used for analysis. Findings: – One of the key findings revolves around the construction of the perceived image of rosé and how this image varies in different markets. Effectively, this study presents an overview of the perceived reputation of rosé in four different market structures, shaped by different cultural and image management issues. Practical implications: – The most crucial implication of this research is the cultural variation in consumer attitudes toward rosé wine and its impact on marketing strategies to effectively target rosé consumers in different markets. Originality/value: – The vast majority of studies on wine consumer behaviour focus on red or white wines, whereas research on consumption of rosé is virtually non-existent. However, recent market trends indicate a growing popularity of rosé wine around the world. The current study is the first to concentrate on rosé as the focal point of research investigation. The study not only offers insights on the perceived image of rosé based on empirical data, but also provides a broader cross-cultural perspective on how this image varies in different markets.